Primers and visualization of LAMP: A rapid molecular identification method for Liposcelis entomophila (Enderlein) (Psocodea: Liposcelididae). (September 2021) - Zeng, Lingyu; Su, Yun; Stejskal, Vaclav; Opit, George; Aulicky, Radek; Li, Zhihong
Abstract: Liposcelis entomophila (Psocodea: Liposcelididae) is one of the most economically important booklice in the world. This species damages stored grain and represents an allergenic health risk to humans. Because of the small size of booklice, they are difficult to identify using morphological characteristics. Traditional molecular identification, such as DNA barcoding and qRT-PCR, requires specialized equipment and takes a long time, which is not appropriate for practical usage by plant health inspectors at ports. Therefore, for storage psocid identification, we suggested a simple, rapid and relatively new technique known as loop-mediated isothermal amplification (LAMP). In our study, a new rapid molecular identification method using the LAMP technique based on the mitochondrial gene cytochrome c oxidase I (COI) was developed for L. entomophila with high specificity and efficiency. Evident amplification results could be presented if the DNA concentration was 0.001 ng/μL. Visual detection was also possible with our LAMP primers using hydroxy naphthol blue (HNB), relying on the clear change in color from violet to sky blue after amplification. This method successfully determined unknown species that were newly collected from grain stores and may facilitate L. entomophila identification in plant quarantine and stored product protection. Highlights: A group of LAMP primers for rapid and specific detection of Liposcelis entomophila was firstly developed. The assay had a detection limit of 0.001 ng/μL L . entomophila DNA per reaction. Visual LAMP made it possible to identify L. entomophila with the naked eye. The primer group was successfully validated using field booklice populations.